2001
DOI: 10.4049/jimmunol.167.5.2457
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Linkage Disequilibrium and Disease-Associated CTLA4 Gene Polymorphisms

Abstract: CTLA4 and CD28 are important regulators of T lymphocyte activation. Gene region 2q33 carrying genes for both CTLA4 and CD28 has been shown to be linked to many autoimmune diseases. Disease associations with particular CTLA4 gene polymorphisms have been reported. Recently, first lines of evidence emerged for functional effects of CTLA4 gene polymorphisms. Two independent studies reported a reduced inhibitory function of CTLA4 in individuals with certain CTLA4 genotypes: those with a high number of microsatellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 21 publications
6
39
0
1
Order By: Relevance
“…Alleles with long repeat regions have been associated with Grave's disease, myasthenia gravis, and multiple myeloma and have been correlated with a decrease in the CTLA-4 inhibitory function in myasthenia gravis [6,19,20]. In agreement with previous reports on allelic frequencies of the CTLA-4 (AT) n polymorphism in Caucasian populations [12,21], we found a high frequency of the short allele (AT) 8 in NHL patients and controls. However, no association of the CTLA-4 microsatellite polymorphism with NHL was detected.…”
Section: Discussionsupporting
confidence: 91%
“…Alleles with long repeat regions have been associated with Grave's disease, myasthenia gravis, and multiple myeloma and have been correlated with a decrease in the CTLA-4 inhibitory function in myasthenia gravis [6,19,20]. In agreement with previous reports on allelic frequencies of the CTLA-4 (AT) n polymorphism in Caucasian populations [12,21], we found a high frequency of the short allele (AT) 8 in NHL patients and controls. However, no association of the CTLA-4 microsatellite polymorphism with NHL was detected.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the presence of the GG genotype resulted in less increase in T-cell proliferation upon blocking CTLA-4 when compared to the AA genotype. Similarly, other investigators have examined the effects of the A and G alleles of the CTLA-4 A/G 49 SNP on the inhibitory function of CTLA-4. [44][45][46] The GG genotype was found to be associated with reduced inhibitory function of CTLA-4 on T-cell proliferation after stimulation with an allogeneic cell line, and with decreased CTLA-4 surface expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the A/G 49 SNP can be used as a surrogate marker until the causative polymorphism is identified. Indeed, preliminary data in myasthenia gravis showed that the (AT)n microsatellite at the 3 0 UTR of the CTLA-4 gene influenced the half-life of the CTLA-4 mRNA, 48,49 and contributed to decreased mRNA stability. 50 This could provide an attractive explanation for the association between the short alleles of the (AT)n microsatellite and AITD, as well as other autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, there is no actual evidence that the CTLA4 þ 49 SNP as such were the genuine susceptibility factor. Owing to strong linkage disequilibrium (LD) in the region, 4 the identification of the primary susceptibility polymorphism may not be an easy task. Also, similar to the HLA loci, there can be multiple alleles or genes playing a role.…”
Section: Introductionmentioning
confidence: 99%